2023
DOI: 10.3389/fneur.2022.882635
|View full text |Cite
|
Sign up to set email alerts
|

Genetic removal of synaptic Zn2+ impairs cognition, alters neurotrophic signaling and induces neuronal hyperactivity

Abstract: Vesicular Zn2+ (zinc) is released at synapses and has been demonstrated to modulate neuronal responses. However, mechanisms through which dysregulation of zinc homeostasis may potentiate neuronal dysfunction and neurodegeneration are not well-understood. We previously reported that accumulation of soluble amyloid beta oligomers (AβO) at synapses correlates with synaptic loss and that AβO localization at synapses is regulated by synaptic activity and enhanced by the release of vesicular Zn2+ in the hippocampus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 120 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Yet, previous investigations provided rather limited data on aged and female mice. Adlard et al ( 2010 ) found a cognitive decline in 3-month-old ZnT mice (mixed-gender) using MWM testing and progressive decline in object location memory (OLM) at 3 and 6-months of age was also reported (also a mixed-gender study; Vogler et al, 2022 ). Here we monitored performance of male and female ZnT mice in NOR, NLR, MWM, Y-, and T-maze tests for up to 9 months of age.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Yet, previous investigations provided rather limited data on aged and female mice. Adlard et al ( 2010 ) found a cognitive decline in 3-month-old ZnT mice (mixed-gender) using MWM testing and progressive decline in object location memory (OLM) at 3 and 6-months of age was also reported (also a mixed-gender study; Vogler et al, 2022 ). Here we monitored performance of male and female ZnT mice in NOR, NLR, MWM, Y-, and T-maze tests for up to 9 months of age.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, insulin resistance in the brain also can damage hippocampal synaptic plasticity leading to abnormal synaptic function (Stranahan et al, 2008 ; Ansari et al, 2023 ). Morphological development of dendrites in hippocampal neurons is regulated by the brain-derived neurotrophic factor (BDNF) (Wang et al, 2015 ) and there are reports indicating that ZnT 3 knockout mice show reduced BDNF expression (Vogler et al, 2022 ). However other studies reported that knocking out ZnT 3 can lead to an increased levels of BDNF in the brain of younger mice, which was linked to increased dendritic length and more intricate connections between neurons (Helgager et al, 2014 ; Yoo et al, 2016 ; McAllister et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zn 2+ dyshomeostasis is related to aging within the cerebral cortex, as well. As the cerebral cortex is involved in high levels of cognitive functions, alterations in Zn 2+ levels within this area could impact cognitive performance in elderly individuals (Vogler et al, 2022). Fluctuations in Zn 2+ distribution, transport, and signaling may contribute to age-related cognitive decline, neurodegenerative diseases, and other age-related neuropathological conditions and psychiatric disorders (Takeda et al, 2018;Marchetti et al, 2022).…”
Section: Zn 2+ As a Function Of Agementioning
confidence: 99%